2016
DOI: 10.1007/s00223-016-0123-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Sarcopenic Obesity and Dynapenic Obesity with Bone Mineral Density and Incident Fractures Over 5–10 Years in Community-Dwelling Older Adults

Abstract: The purpose of this study is to determine whether low muscle mass (sarcopenia) or strength (dynapenia), in the presence of obesity, are associated with increased risk for osteoporosis and non-vertebral fracture over 5-10 years in community-dwelling older adults. N = 1089 volunteers (mean ± SD age 62 ± 7 years; 51 % female) participated at baseline and 761 attended follow-up clinics (mean 5.1 ± 0.5 years later). Total body, total hip and spine BMD, and appendicular lean and total fat mass were assessed by DXA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
3
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(122 citation statements)
references
References 32 publications
3
106
3
4
Order By: Relevance
“…Similarly, Yu and colleagues reported that sarcopenia predicted fractures in the Chinese cohort of the MrOS study and additionally showed improved fracture prediction when combined with FRAX. Similar observations were reported for sarcopenic obesity and osteosarcopenic obesity . Although previous data from the US MrOS study found that impaired physical function predicted hip fractures, current sarcopenia definitions did not consistently predict fractures .…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, Yu and colleagues reported that sarcopenia predicted fractures in the Chinese cohort of the MrOS study and additionally showed improved fracture prediction when combined with FRAX. Similar observations were reported for sarcopenic obesity and osteosarcopenic obesity . Although previous data from the US MrOS study found that impaired physical function predicted hip fractures, current sarcopenia definitions did not consistently predict fractures .…”
Section: Discussionsupporting
confidence: 80%
“…Sarcopenic and dynopenic obese individuals appear to be at a greater risk for lower BMD and higher fracture risk than obese individuals with normal muscle mass and strength (Scott, et al 2016). This interpretation is consistent with studies reporting that obese osteopenic individuals are at a higher fracture risk compared to normal weight osteopenic individuals (Cawsey, et al 2015).…”
Section: Scaling Bone Mass To Body Weightmentioning
confidence: 99%
“…Reduced muscle mass synergistically accompanies accumulation of fat mass, resulting in sarcopenic obesity [3]. Compared to obesity alone, sarcopenic obesity is associated with a heightened risk of adverse health outcomes, such as disability or impairment, cardiometabolic diseases, other comorbidities, and mortality [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%